Earnings management and firm performance of seasoned equity offerings in select African securities markets - Njau, Daniel Kungu (My University, 2021)
The pursuit of finance is an iterative undertaking for finance executives globally intending to attain he desired level of financing. Primarily, managers and investors communications take place through financial statements; hence the statements information veracity possess far-reaching implications for the future of the firm on one hand and investor wellbeing on the other hand. However, various agency issues crop up, which interfere with the content of earnings reported, critical among them is Earnings Management (EM). EM refers to the practice of applying various accounting techniques and practices that present an overly optimistic view of the financial statements. EM is an emerging issue, which is increasingly attracting public attention, attributable to a crisis of confidence enveloping financial statements in the wake of recent global financial scandals. In summary, EM is a contemporary financial aspect that ultimately affects financial statements through influencing investors’ decision making and impacting on firm performance. Chiefly, this thesis seeks to investigate the presence and extent of EM in seasoned equity offerings (SEOs) and its effect on the short and long-run performance of these SEOs in the African emerging securities markets. The offshoot objectives of this study include examining the decomposition of EM into accruals EM (AEM) and real EM (REM) respectively and investigating topical issues that impact or are impacted by EM. These include corporate governance, earnings quality, and information asymmetry. To achieve the stated objectives, the study examines 550 SEOs from 12 select African markets for the period 2008 to 2018. The modified Jones model and the Roychowdhury model are used to compute AEM and REM, respectively. Additionally, several panel data econometric approaches are used, namely System GMM for the dynamic model, Instrumental Variables as well as a linear model. The findings confirm the presence and extent of EM in African emerging markets and build on the existing knowledge on EM in SEOs by advancing two main contributions. Firstly, the prevalence of EM is higher in SEOs compared to non-SEOs. Moreover, results also suggest that an improved level of financial performance in the pre-SEO issuance period is usually followed by impaired performance in the long run. Secondly, EM deteriorates earnings quality while information asymmetry exacerbates it. However, corporate governance proves to be a useful tool in mitigating EM to a limited extent. The results from this study have a policy implication in two main ways. Firstly, public knowledge of EM practices will guide investors in critically evaluating SEOs for their real future intrinsic and potential value. Through examining the effects of EM, keen investors will be able to distinguish future earnings surprises and optimistic financial reporting. Secondly, where managers engage in EM, which is pervasive and shows evidence of detrimental effects on shareholder value, policy standards can be enacted to mitigate against EM
A thesis submitted to the School of Economics and Finance, Faculty of Commerce, Law and Management, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021